How Visually Challenged People Understand the Film with Audio Description - Raj R, Prathyush (Journal of Advanced Research in Journalism & Mass Communication, 2022)
This research study focuses on how Audio description helps the visually challenged students to understand the narration of a movie, The researcher used qualitative research method to collect the data, he conducted an in-depth interview with 52 visually challenged school students who are aged between 10 to 16 years old from poonamalli blind school which is in Chennai. The researcher took convenience sampling which is a type of non probability sampling method in drawing the population. The researcher conducts screening of a episode from a Tamil web series named Suzhal the vortex with and without Audio Description.The researcher asks 25 open-ended questions and collect information from every 52 participants individually. The researcher finds that the research is successful in finding out results positively using Audio Description. How to cite this article: Raj RP. How Visually Challenged People Understand the Film with Audio Description. J Adv Res Jrnl Mass Comm 2022; 9(3): 11-14. DOI: https://doi.org/10.24321/2395.3810.202203